Analysis of The Implementation of The Merdeka Curriculum on Essential Science Materials at SMPN 1 Gerung. - Muhamad Hendri Diarta; Ni Ketut Anggriani; Fitri Muslihatun; Syamsul Madani (Indonesian Journal of STEM Education, 2026)
The Merdeka Curriculum is the latest curriculum developed by the Indonesian Ministry of Education, Culture, Research, and Technology to provide more flexible learning, competency-oriented instruction, and character development through the Pancasila Student Profile. This study aims to analyze the implementation of the Merdeka Curriculum on essential science materials at SMPN 1 Gerung, focusing on three aspects: lesson planning, learning implementation, and learning evaluation. This research employed a descriptive qualitative method with a case study approach. Data were collected through observation, questionnaires, and semi-structured interviews involving three science teachers who actively implement the Merdeka Curriculum at the school. The results indicate that the implementation of the Merdeka Curriculum at SMPN 1 Gerung has been carried out effectively. Teachers have prepared teaching modules based on learning outcomes and implemented contextual learning activities through simple project-based learning. Despite limited laboratory facilities and learning resources, teachers demonstrated adaptive strategies by utilizing simple materials, contextual experiments, and digital resources to support learning activities. The findings also show that teachers prioritize essential science materials based on Learning Outcomes (CP) to ensure conceptual understanding and scientific process skills development. Overall, the implementation of the Merdeka Curriculum shows positive progress; however, strengthening teacher competence and providing sustainable training and facilities remain necessary.